Can novel adipokines, asprosin and meteorin-like, be biomarkers for malignant mesothelioma? - Kocaman, N.; Artas, G. (Taylor & Francis Ltd, 2020)
Malignant mesothelioma (MM) is a rare tumor of serous surfaces that has a poor prognosis. Cancer is a multistage process by which cells undergo metabolic and behavioral changes that cause excessive and untimely proliferation. Asprosin (ASP) and meteorin-like (METRNL) are two peptides associated with glucose and energy metabolism. We used immunohistochemistry to investigate whether these peptides could be biomarkers for diagnosis and treatment of MM. We reviewed 30 cases of MM and 30 cases of reactive mesothelial hyperplasia (RMH); we used the cases with RMH as control group. The specimens were examined using immunohistochemical staining for ASP and METRNL. ASP and METRNL immunoreactivity was more prominent in the MM specimens than the RMH specimens. Therefore, ASP and METRNL potentially could be used as markers for differentiating MM from benign diseases.
Keywords: Adipokines; asprosin; biomarkers; immunohistochemistry; mesothelioma; meteorin-like